Trend, causes and determinants of perinatal deaths in Ondo state: insights from maternal and perinatal death surveillance and response data 2021-2022 - Aladeniyi, Isaac O.; Oluwafemi, Rosena O. (International Journal of Research in Medical Sciences, 2026)
Background: Perinatal mortality remains a major public health challenge in Nigeria and it contributes substantially to under-five mortality. Maternal and perinatal death surveillance and response (MPDSR) systems provide opportunities to identify patterns, causes, and avoidable factors associated with these deaths. This study assessed MPDSR implementation and examined the trends, causes, and determinants of perinatal deaths in Ondo State, Nigeria, between 2021 and 2022. Methods: A retrospective descriptive study was conducted using triangulated MPDSR data obtained from the electronic MPDSR platform, district health information system (DHIS-2), and health facility records in Ondo State. A four-phase review process involving desk review, stakeholder engagement, data mapping, facility-level record harvesting, and database validation was adopted. Data were extracted using National MPDSR tools and analysed with SPSS version 23 using descriptive statistics. Results: A total of 365 and 392 perinatal deaths were notified in 2021 and 2022 respectively, of which 68 (18.6%) and 133 (33.9%) were reviewed. Most deaths occurred in health facilities. Home referrals accounted for 28 (41.2%) of reviewed cases in 2021 and 24 (18%) in 2022. Macerated stillbirths constituted a substantial proportion of deaths, while birth asphyxia, prematurity and sepsis were the leading causes. Delayed presentation, poor referral systems, socioeconomic barriers, and inadequate intrapartum monitoring were major contributory factors. Conclusions: Structural and systemic barriers accounted for significant perinatal losses. Therefore, strengthening MPDSR systems, improving intrapartum care, regulating non-skilled birth practices, building the capacity of health workers and expanding equitable maternal and newborn services are essential to reducing preventable perinatal deaths.